Proceedings of the 12th Annual Conference on Cyber and Information Security Research 2017
DOI: 10.1145/3064814.3064832
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating eavesdropping attacks in software-defined networking data plane

Abstract: Software-De ned Networking (SDN) is an emerging paradigm that introduces a concept of programmable networks to enhance the agility in networking management. By separating concerns of the data plane and the control plane, implementing network switching as packet forwarding, and using centralized software to logically control the entire networks, SDN makes it simpler to automate and con gure the network to respond to high-level policy enforcement and dynamically changing network conditions. As SDN becomes more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Therefore, n-k threshold principle is used to resist passive eavesdropping. In order to improve the diversity of forwarding paths, Aseeri et al [74] designed bidirectional multipath routing algorithm. By negotiating migrating paths between source and destination, forwarding path is changed randomly during net-flow transmission.…”
Section: Single-layer Mtd Transformation Mechanism In Networkmentioning
confidence: 99%
“…Therefore, n-k threshold principle is used to resist passive eavesdropping. In order to improve the diversity of forwarding paths, Aseeri et al [74] designed bidirectional multipath routing algorithm. By negotiating migrating paths between source and destination, forwarding path is changed randomly during net-flow transmission.…”
Section: Single-layer Mtd Transformation Mechanism In Networkmentioning
confidence: 99%
“…As each route transmits only a portion of the packets exchanged during the communication, even though the eavesdropper is well positioned in a strategic point of the network, he will not be able to intercept an entire communication between two devices. As the multipath routing strategy always relies on the shortest path to transmit the acknowledgment (ACK) packets from the receiver, Aseeri et al [145] found that an attacker can still capture all the packets by eavesdropping on the shortest path and blocking the ACK packet corresponding to the packet sent through other routes until it is retransmitted via the path he is listening to. To address this defect, the SDN controller can be utilized to instruct the receiver to send the ACK packet via the path used by the sender.…”
Section: Benignmentioning
confidence: 99%
“…[102], [103], [104], [105], [106], [107], [108] Segmentation ✓ ✓ [116], [117] Reconfiguration Isolation and Containment ✓ ✓ ✓ ✓ [118], [119], [120], [121], [122], [123] Dynamic Network Composition ✓ ✓ [101], [124], [125], [126], [127] Non-Persistence ✓ ✓ [128], [129] Moving Target Defense (MTD) [138], [139], [140], [141], [142], [143], [144],…”
Section: Risk Management Vs Cyber-resiliencementioning
confidence: 99%